Adjusted Risk Stratification of Indeterminate Thyroid Nodules Using the American College of Radiology Thyroid Imaging Reporting and Data System (ACR TI‐RADS) - Jessica Zhao; Rita Abi‐Raad; Sara I. Pai; Jonathan Langdon; Minhua Wang; Guoping Cai; John Sinard; Adebowale J. Adeniran; Sanhong Yu (Cancer Medicine, 2026)
ABSTRACT Background The TI‐RADS guides the initial management of thyroid nodules, but the malignancy risk across different categories of cytologically indeterminate thyroid nodules (CITNs), particularly AUS and FN, remains unclear. Methods We reviewed thyroid FNA specimens diagnosed as AUS or FN with TI‐RADS scores of 3, 4, or 5 from 2017 to 2025. Clinical data, molecular results, and surgical outcomes were analyzed. Results A total of 919 CITNs were identified: 304 with TI‐RADS 3, 454 with TI‐RADS 4, and 161 with TI‐RADS 5. In the absence of molecular alterations, the risk of malignancy (ROM) was low for AUS and FN in both TI‐RADS 3 and 4 categories (< 10%). In contrast, TI‐RADS 5 nodules diagnosed as AUS or FN had the highest ROM (56%). ROM similarly increased with the TI‐RADS score. For AUS, ROM was 14% (TI‐RADS 3), 31% (TI‐RADS 4), and 60% (TI‐RADS 5). For FN, ROM increased from 26% to 44% to 57% across TI‐RADS 3, 4, and 5, respectively. Notably, even AUS nodules without detectable mutations had a high ROM of 44% in TI‐RADS 5, compared to 10% and 15% in TI‐RADS 3 and 4, respectively. Conclusion Our findings demonstrate distinctive ROMs among AUS and FN stratified by TI‐RADS category and underscore the variable utility of molecular testing. TI‐RADS 5 CITNs carry a significantly higher ROM even in the absence of molecular alterations, suggesting the importance of combining TI‐RADS and TBSRTC.